Arabic Advertising on Food Products and Beverages: A Stylistic Analysis dan Semantic Field - Novianti , Lisa; Rifai, Alimudin; R. Saleh, Sriwahyuningsi; Pallawagau, Baso (Language Development Center, 2022)
Background: Many foods and beverage products are currently using Arabic as advertisements to promote product contents and explain how to present them in a contemporary language style to make it easier for consumers from across countries. Purpose: This study aims to (1) describe the process of forming Arabic vocabulary advertised on food and beverage products and (2) find out the meaning and style of Arabic used in food and beverage products. Method: This study applies a stylistic and semantic field approach to library research. Primary data was collected and identified through seven product advertisements serving food and beverages. Data were analyzed descriptively through the identification of vocabulary, analysis of the use of advertising language style, and variants of meaning. Results and Discussion: The results of this study indicate that there is a similarity in the use of imperative sentences in the manner of presenting products, the advertising language used to explain how to present food and beverage products always uses the style of uslub al-Amr (command word) to do something. In addition, the word forms used have ten different meanings according to the context of the sentence. Conclusions and Implications: The results of this study have implications for acquiring new Arabic vocabulary with contemporary advertising language styles, which can be done by studying product presentation instructions.